Stridor in children: croup or something more sinister? A case of subglottic cyst - Mohd Hisham Mohd Isa,; Tan, Toh Leong; Fadzlon Mohd Yatim, (Fakulti Perubatan, UKM, 2016)
Stridor in infants with subglottic cyst is rare. Mismanagement of such cases may lead to respiratory compromise with a potentially serious and fatal outcome. The diversity of the clinical presentations throws a great challenge in the diagnosis of subglottic cysts. Manifestations vary as they depend on the size and location of the cysts. We report the case of a 6-month-old girl who had a subglottic cyst but managed as moderate croup till she developed worsening respiratory acidosis which difficult intubation. Any case of premature infants with previous history of neonatal intubation presenting with stridor should prompt clinicians to look for possible cysts in the larynx. This is important because once the diagnosis is made, appropriate treatment may be given and unnecessary morbidity and mortality may be avoided.